2018
DOI: 10.1098/rsos.180448
|View full text |Cite
|
Sign up to set email alerts
|

Data availability, reusability, and analytic reproducibility: evaluating the impact of a mandatory open data policy at the journal Cognition

Abstract: Access to data is a critical feature of an efficient, progressive and ultimately self-correcting scientific ecosystem. But the extent to which in-principle benefits of data sharing are realized in practice is unclear. Crucially, it is largely unknown whether published findings can be reproduced by repeating reported analyses upon shared data (‘analytic reproducibility’). To investigate this, we conducted an observational evaluation of a mandatory open data policy introduced at the journal Cognition. Interrupte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
266
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(295 citation statements)
references
References 56 publications
10
266
3
1
Order By: Relevance
“…Data sharing also provides opportunities for science to correct itself by allowing independent review of data analysis (e.g., Hardwicke et al, 2018). Finding errors in published work is painful, as many researchers know from personal experience.…”
Section: Openness Maximizes the Value Of Researchmentioning
confidence: 99%
“…Data sharing also provides opportunities for science to correct itself by allowing independent review of data analysis (e.g., Hardwicke et al, 2018). Finding errors in published work is painful, as many researchers know from personal experience.…”
Section: Openness Maximizes the Value Of Researchmentioning
confidence: 99%
“…Because p values are not always reported exactly, and because there might be errors in computing p values (see Nuijten et al, 2016;Hardwicke et al, 2018), we re-compute p values when possible from test statistics and degrees of freedom extracted from the source paper (i.e. F scores, t -values, etc).…”
Section: Planned Analysesmentioning
confidence: 99%
“…For example, in a study of 21 orthopaedic surgery journals, Checketts et al reported that 52% required clinical trial registration 10 . Furthermore, several studies have examined the implementation of data-sharing policies, finding that their enactment led to an increase in the publications that included raw data 11,12 . With publication retractions in orthopaedics increasing, primarily due to academic misconduct and fraud 13 , the need to verify trials by reproducing studies has become more urgent.…”
Section: Introductionmentioning
confidence: 99%